(untitled) (Transport systems and technologies, 2018)
The results of research on the definition of effective methods for increasing the performance of rail brake systems with the use of expert evaluation are highlighted. The following innovative methods for improving the efficiency of the braking system of the modern rolling stock are considered: air supply to the contact of triboelements; forced air supply, the temperature of which is regulated depending on the conditions and modes of operation; application of pads with powdered inserts; application of pads with cooling fins; the application of brake linings whose outer surface is made of te-folding material; supply to the contact zone of triboelements of friction activators; application of brake elements, in the construction of which are provided phase transitions. The rail brake system is a complex technical system, the quality of which is determined by many criteria: functional, reliable-removing, cost, energy, resource, time, technical, social, environmental, etc. The creation of brake elements is a multi-criteria, statistical, non-deterministic decision-making problem. Among the options for constructive performance and performance improvement methods, the most effective ones are needed. Methods of expert assessments include the organization of robotics with expert experts in processing their opinions expressed in quantitative and / or qualitative form in order to prepare information for the decision maker.